COMPARATIVE EFFECTS OF BIOLOGICS IN PREVENTING PENETRATING COMPLICATIONS IN CROHN'S DISEASE. (26th January 2023) - Deepak, Parakkal; Stwalley, Dustin; McCurdy, Jeffrey
Abstract: BACKGROUND: Comparative efficacy of biologics is an important consideration when selecting therapies for Crohn's disease (CD). While recent studies have focused on clinical remission, few studies have assessed the comparative efficacy of biologics in preventing penetrating disease (PD) complications of CD. The aim of our study was to compare the rates of penetrating complications (luminal and perianal) between biologics used as first-line therapies in CD. METHODS: A propensity-score adjusted retrospective comparative effectiveness study was performed using IBM® MarketScan® Commercial Database (2006-2020). We included adults (≥18 years) with CD (≥3 administrative claims for CD [K50.*]) who initiated their first biologic (anti-tumor necrosis factor [anti-TNF], ustekinumab ([UST]) or vedolizumab [VDZ]). with ≥ 2 consecutive years of health insurance enrollment during study period (at least 1 year following index date). Patients with pre-existing luminal penetrating disease (LPD) or perianal penetrating disease (PPD) or prior biologic exposure were excluded using a minimum look-back period of 1 year. LPD was identified by ICD claims (537.4, 567.2X, 569.X, 593.82, 596.1, 619.1, K31.6, K65.X, K63.X, N82, N32.1) and PPD by a validated case definition. Patients were followed until a PD event and censored if a new biologic class was initiated, loss of medical coverage or study end. Cohorts were balanced by inverse probability of treatment weighting based on age, sex, Elixhauser comorbidity score, and prior CD surgery. Pairwise comparisons of biologic classes were performed by cox-proportional hazard models with medication exposure treated as a time-dependent variable based on a medication possession ratio of 0.8. RESULTS: A total of 40693 patients with CD without prior penetrating disease (54.1% female, median age 39 years [IQR; 28-50]) initiated biologic therapy: 37839 (93.0%) anti-TNF, 1194 (3.0%) UST and 1660 (4.0%) VDZ. Penetrating complications developed in 8567 (21.1%) patients: 2, 204 (5.4%) LPD and 7, 474 (18.4%) PPD. Compared with no medication exposure, anti-TNFs were protective against composite (Figure 1, HR 0.91; 95% confidence interval (CI), 0.84 - 0.98, p = 0.013) and LPD (HR 0.59; CI, 0.50 - 0.69; p <.0001) but not PPD (HR, 0.99; CI, 0.91 - 1.07; p = 0.78). Neither VDZ nor UST were protective against composite, LPD or PPD. In pairwise comparisons, anti-TNF was significantly protective against composite (Figure 2, HR 0.92; CI, 0.85 – 0.99; P = 0.018) and LPD (HR 0.51; CI, 0.44 – 0.60; p <.0001) compared with VDZ and for LPD compared with UST (HR, 0.71; CI, 0.61 – 0.83, p <.0001). CONCLUSIONS: Anti-TNF therapy was protective against developing LPD and may offer an advantage over VDZ and UST in preventing this disease complication. Further studies are needed to validate these findings and to determine potential reasons for these differences. Figure 1: Comparison of biologics in preventing the composite outcome of penetrating complications in patients with Crohn's disease. Figure 2: Comparison of anti-TNF versus vedolizumab in preventing composite outcome of penetrating complications in patients with Crohn's disease